Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am suppose to use the substitution of $u = x + y$

$y' = x + y$

$u(x) = x + y(x)$

I actually forget the trick to this and it doesn't really make much sense to me. I know that I need to get everything in a variable with x I think but I am not sure how to manipulate the problem according to mathematical rules that will make sense. Also I know that at some point I will get an integral or something and that I have no idea how to do that with multiple variables.

share|improve this question
add comment

2 Answers 2

up vote 5 down vote accepted

$$y'=x+y$$

Then we let $u=x+y$

This gives $u'=1+y'$, so that the equation becomes

$$u'-1=u$$

$$u'-u=1$$

Can you solve that for $u$?

Hint $(e^x-1)'=e^x$

Moving on with the solution:

$$\frac{du}{dx}-u=1$$

$$\frac{du}{dx}=1+u$$

And the classic abuse in DE's

$$\frac{du}{u+1}=dx$$

Now

$$\int\frac{du}{u+1}=\int dx$$

$$\log(u+1)=x+C$$

We take logarithms

$$u+1=e^{x+C}$$

We use the property of the exponential function $f(x+y)=f(x)f(y)$

$$u+1=e^C e^x$$

Here $K=e^C$

$$y+x+1=Ke^x$$

$$y=K e^x-x-1$$

share|improve this answer
    
This does not appear to be a seperable equation and that is all I know how to do. –  user138246 Jun 18 '12 at 0:36
1  
Well, you're supposed to use the method of integrating factor, so multiply both sides by $\exp(x)$, and then you get $(u'-u)\exp(x)=\exp(x)$. The left hand side is $(u\cdot\exp(x))'$, and you can integrate everything nicely. –  Alex Nelson Jun 18 '12 at 0:38
    
@AlexNelson No one is supposed to do anything. One can choose a variety of paths. In this case, noting that $e^x-(e^x-1)=1$ is one simple solution. I don't think he knows about IFs. –  Pedro Tamaroff Jun 18 '12 at 0:42
1  
@PeterTamaroff I know I don't know acronyms :$ what does IF stand for? –  Alex Nelson Jun 18 '12 at 0:43
    
@AlexNelson "use the method of **i**ntegrating **f**actor" –  Pedro Tamaroff Jun 18 '12 at 0:46
show 14 more comments

Well, if $u = x + y$, then $y = u - x$. Take the derivative to both sides and we get $$ y' = u' - 1 $$ set this equal to the right hand side of our differential equation $$ u' - 1 = x + y $$ But our substitution is $u=x+y$, so the right hand side simplifies becoming $$ u' - 1 = u$$ thus we get a differential equation $$ u' = 1 + u. $$ This can be solved, then we plug it back into the substitution to solve for $y$.

share|improve this answer
    
I still get a funtion I do not know how to work with. I do not know how to find the integral of something without a dy or dx or whatever. –  user138246 Jun 18 '12 at 0:41
2  
Well, you're supposed to divide both sides by $1+u$, right? You get $u'/(1+u)=1$. Integrate both sides with respect to $x$, so you get $\int (1+u)^{-1}\,du = \int dx$. Performing this integral gives you $\ln(1+u) = x-x_{0}$. Exponentiate both sides, and you're almost done... –  Alex Nelson Jun 18 '12 at 0:42
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.